Tribal situation in India (Vol.6) - Behera,Deepak Kumar (ed.); Pfeffer,Georg (ed.) (New Delhi, 1997)
Documentation of various facets of tribal social reality is very much Essential before they are totally eclipsed by the rapid process of Globalization of the World economy. While examining the current literature on tribal Societies we notice a curious absence of Scientific studies based on intensive fieldwork among a Large and important section of the world population. The series Contemporary Society : Tribal Studies tries to fill in this gap and thereby attempts to remove our ignorance on many aspects of tribal world. The ongoing series has already brought out five earlier volumes, namely : 1. Structure and Process 2. Development Issues, Transition and Change 3. Social Concern and 4. Social Realities 5. The Concept of Tribal Society This volume, consisting of seventeen papers, presents a Picture of contemporary tribal situation in India. Dealing with the definitional problem of the term 'tribe', it addresses various issues concerning tribal development, changing Cultural patterns, social networks, and tribal health. Also, it analyses the impact of displacement and changing Economy on tribal women. About the Author Georg Pfeffer is Professor and Head of the Department of Ethnology, Freie University of Berlin (Germany). Deepak Kumar Behera is Professor in the Department of Anthropology, Sambalpur University, Sambalpur, Orissa (India)
Keywords: Tribes-India